2018
DOI: 10.1038/s41598-018-19945-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Conductivity of Polyimide Composites with Boron Nitride Nanosheets

Abstract: A strategy was reported to prepare boron nitride nanosheets (BNNSs) by a molten hydroxide assisted liquid exfoliation from hexagonal boron nitride (h-BN) powder. BNNSs with an average thickness of 3 nm were obtained by a facile, low-cost, and scalable exfoliation method. Highly thermally conductive polyimide (PI) composite films with BNNSs filler were prepared by solution-casting process. The in-plane thermal conductivity of PI composite films with 7 wt% BNNSs is up to 2.95 W/mK, which increased by 1,080% comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 47 publications
2
60
0
Order By: Relevance
“…Solution‐casting process was used for the preparation of thermally conductive polyimide/BNNS composite films. [ 186 ] Figure 17(b) indicates the thermal conductivity of neat PI and PI composite films with 7 wt% BNNSs. They found that the in‐plane thermal conductivity was increased by 1,080% where as out‐of plane thermal conductivity was increased by only 76% compared to neat PI.…”
Section: Polymer/boron Nitride Nanocomposites: Classificationsmentioning
confidence: 99%
“…Solution‐casting process was used for the preparation of thermally conductive polyimide/BNNS composite films. [ 186 ] Figure 17(b) indicates the thermal conductivity of neat PI and PI composite films with 7 wt% BNNSs. They found that the in‐plane thermal conductivity was increased by 1,080% where as out‐of plane thermal conductivity was increased by only 76% compared to neat PI.…”
Section: Polymer/boron Nitride Nanocomposites: Classificationsmentioning
confidence: 99%
“…The nano-sized llers, especially for metal or carbon nanomaterials with excellent thermal conductivity, can generally achieve signicant enhancement at a low lling (<15 wt%). It is noteworthy that only 7 wt% BNNS fabricated by the efficient exfoliation of BN nanosheets increased the thermal conductivity by 1080%, 14 which is similar to the enhancing effect of the conventional BN of more than 30 wt%. Apparently, great attention has been paid to the synergism of the llers hybrid for further improvement of the thermal conductivity.…”
Section: Thermal Conductivity Of Pi Composite Lmsmentioning
confidence: 66%
“…11,12 In recent years, in order to solve this contradiction, researchers have proposed four novel strategies. The rst is to design new thermally conductive llers, such as awless graphene, 13 exfoliated BN nanosheet (BNNS) 14 and BN nanotubes. 15 The second is to construct a three-dimensional thermally conductive network by a novel method, such as electrostatic spinning, 16 chemical vapor deposition (CVD), 17 template method, [18][19][20] freeze-drying method, 21 and segregated structure method.…”
Section: Introductionmentioning
confidence: 99%
“…The c‐ BN, due to its hardness, can be used as an abrasive material. While the excellent electrical resistivity of and thermal conductivity of BN makes the use for heat spreaders, the exfoliated hexagonal nanosheets can enhance the thermal conductivity of polymer materials . Other scientific fields where h‐ BN‐based materials can be found involve electrochemistry, biosensing, and even antibacterial properties .…”
Section: Figurementioning
confidence: 99%